2010
DOI: 10.1016/j.schres.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Cortical surface characteristics among offspring of schizophrenia subjects

Abstract: Background-A systematic study of cortical surface parameters in adolescent offspring of schizophrenia subjects before clinical manifestation could clarify neurodevelopmental antecedents of increased genetic risk. We examined these measures obtained on structural magnetic resonance imaging (MRI) scans at baseline and one year on a series of offspring and healthy subjects.Methods-We measured cortical surface area, curvature and thickness using BRAINS2 on structural MRI scans acquired using 1.5T GE whole body sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
40
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 55 publications
9
40
0
Order By: Relevance
“…Apart from deficient myelination, potential pathological mechanisms could include changes of water content in myelin, increased MR-visible axonal cytosol resulting from alterations in the microtubular density of axons, and neuronal degeneration, amongst others [62]. A previous study on adolescents at risk for schizophrenia suggested cortical volumetric, shape and thickness measures as parameters that are differentially linked to neurodevelopmental processes [63]. However, the cortical gyration is hardly comparable to the morphology of the brainstem.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from deficient myelination, potential pathological mechanisms could include changes of water content in myelin, increased MR-visible axonal cytosol resulting from alterations in the microtubular density of axons, and neuronal degeneration, amongst others [62]. A previous study on adolescents at risk for schizophrenia suggested cortical volumetric, shape and thickness measures as parameters that are differentially linked to neurodevelopmental processes [63]. However, the cortical gyration is hardly comparable to the morphology of the brainstem.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cortical thickness and surface area are products of two welldifferentiated ontogenetic processes and the two parameters can therefore separately be affected by genetic defects or extrinsic factors . One study on adolescent first-degree relatives of schizophrenia patients demonstrated reduction in surface area, along with only a slight increase in cortical thickness in a one-year followup study, suggesting different neurodevelopmental trajectories (Prasad et al, 2010).…”
Section: Developmentmentioning
confidence: 99%
“…Structural MRI has shown that the children of schizophrenia patients display some cortical and subcortical brain abnormalities in regions such as the fronto-parietal lobes (Prasad et al, 2010), superior temporal gyrus (Rajarethinam et al, 2004), caudate (Rajarethinam et al, 2007), and the amygdala and hippocampus (Keshavan et al, 2002). Functional imaging studies, including positron emission tomography (PET) and task-based blood oxygenation level dependent (BOLD) functional MRI (t-fMRI) have also been used to explore brain activity alterations in relatives of schizophrenia patients.…”
Section: Introductionmentioning
confidence: 99%